Effects of Spanish vocabulary knowledge on the English word knowledge and listening comprehension of bilingual students. Issue 6 (3rd July 2022) - Luft Baker, Doris; McCoach, Betsy D.; Ware, Sharon; Coyne, Michael D.; Rattan, Susan M.
ABSTRACT: The purpose of the current study was to examine the influence of L1 (i.e. Spanish) receptive vocabulary on both expressive and receptive knowledge of target vocabulary words taught through L2 (i.e. English) instruction and intervention. Participants were Bilingual US kindergarten students determined to be at-risk based on English receptive vocabulary. To determine student vocabulary level in Spanish, we administered a receptive Spanish vocabulary assessment. Students were grouped into matched clusters within classrooms. Clusters were randomly assigned to receive whole group vocabulary instruction only in L2 (i.e. the control group, n = 172) or whole group plus small group vocabulary instruction in L2 (i.e. the treatment group, n = 179). Findings indicated that bilingual students with high receptive vocabulary knowledge in Spanish significantly outperformed bilingual students with low receptive vocabulary knowledge in Spanish. Effects of Spanish vocabulary knowledge were maintained one year later, at the end of first grade, as measured by a researcher developed expressive vocabulary measure in English. We did not find an interaction effect between condition and student level of Spanish receptive vocabulary. Implications for research and practice are discussed.